Gestão pública e política curricular : a materialidade da educação das relações étnico-raciais na educação básica do estado de Mato Grosso - Ribeiro, Cândida Cespedes (2016)
The present study analyzes the institutional relationship of the State Department of Education of Mato Grosso (Seduc-MT) with the process of construction and conduction of the Curricular Policy of Ethnic-Racial Relations Education, as recommended by the National Curricular Guidelines for Ethnic Relations Education -Racial and for the Teaching of AfroBrazilian and African History and Culture, arising from the changes brought by Law 10.639 / 2003 to the Law on Guidelines and Bases of National Education (LDB nº 9.394 / 1996). From the perspective of public managers in the State of Education of Mato Grosso (Management 2015-2018), aims to understand the process of materiality of this policy in the State Basic Education. Specifically, it was sought to recover the debate present in state official texts and, later, by conducting interviews with public administrators who were in Management in the year 2015, reflect on the performance of Seduc-MT with regard to the Public management of the Education Curricular Policy for Ethnic-Racial Relations, as well as its possible developments in the field of School Curriculum and Continuing Education of Professionals of Basic Education in the State of Mato Grosso. The research is developed under the qualitative approach, making use of methodological procedures that include bibliographic research and documentary research, as well as the interview as data collection technique. The method adopted then involves exploring, describing and evaluating the research object, which is the construction and public administration of this Curricular Policy in Basic Education in Mato Grosso. The methodology is based on the dialectic, since according to Severino (2007), knowledge can not be understood in isolation from the political practice of men, because it is never a question of knowing only, but also of power. The research subjects are public managers, four of whom are interviewed: the Secretary of State for Education; The Assistant Secretary for Educational Policies; The Superintendent of Vocational Training of the Basic Education Professionals and the Superintendent of Educational Diversities. We use the analytical methodological framework of the "Policy Cycle" formulated by Bowe and Ball (1992), because through it we revisit, contextualize and analyze public policies for the Education of Ethnic-Racial Relations contained in official texts and in speeches of the interviewees. The analyzed data reveals through texts that there is a distance between the formal materiality (discussion / definition / presentation) of the Education Curricular Policy of Ethnic-Racial Relations and the speeches about its interpretation and exercise in the Basic Education of the State of Mato Grosso, Especially with regard to the production and dissemination of knowledge that fosters attitudes, attitudes and values that educate citizens regarding ethnic-racial plurality, demonstrating that the public management of this affirmative policy managed by Seduc-MT has not yet been able to assure its full materiality In local basic education.